Perencanaan Proyek Pendirian Bimbingan Belajar Mari Smart - Agung Wijoyo; Atina Fahma Rosyada; Ikhwan Sukirman Ikhwan Sukirman; Muhammad Afrizal Nur; Rezky Arianda (CV. Multi Kreasi Media, 2022)
Tutoring is a process of providing learning assistance to individuals which is carried out continuously to produce a change in the individual. This is of course done to help increase students' interest in learning by creating learning patterns that are made more efficient and fun so that they are more easily accepted by tutoring students. Tutoring Institutions are non-formal educational institutions that are intended to help improve students' knowledge and skills regarding subjects received at formal educational institutions, or supplement them with lessons and specializations that are not studied at formal educational institutions. Planning for a tutoring project establishment is certainly not a type of business that can be carried out by anyone, because it requires high competence and integrity in order to educate the life of the Indonesian people.